Evaluasi Pendidikan Dalam Perspektif Filsafat Pendidikan Islam - Arzi Shafaunnida (STIT Muhammadiyah Paciran, 2022)
Evaluation in Islamic education is generally very useful for educators, learners, thinkers of Islamic education, politics of Islamic education policy makers, to assist them in improving the supervisory system and considering the policies that will be applied in the national education system (Islam). Research Library or Library research is the study of several references related to research conducted both the thinking of the figures and others. evaluation is a process and action planned to collect information about progress, growth and development (learners) of the purpose (education), so that can be compiled assessment that can be used as a basis for making decisions. Evaluations are conducted to evaluate learners, educators, educational materials, the process of delivering subject matter, and various other aspects related to educational materials.